Analisis Risiko Penyakit Akibat Kerja Pada Crew Sound System dengan Metode HIRARC - Achmad Yogi Arifudin; Asri Dwi Puspita (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The work of sound system crews involves transporting, installing, operating, and dismantling heavy, high-tech audio equipment, often over long shifts. These conditions can lead to physical fatigue, work-related stress, and musculoskeletal or hearing disorders. However, the implementation of Occupational Health and Safety (OHS) measures in this sector remains limited, meaning that hazard risk identification has not been conducted systematically. Therefore, this study aimed to analyze the risk of occupational illnesses among sound system rental workers using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method. The findings indicate that several work activities entail risks ranging from moderate to high, including muscle pain, back pain, physical fatigue, sleep disturbances, hearing impairment, tinnitus, excessive stress, and electric shock. To mitigate these risks, it is recommended that sound system crews use trolleys, employ proper manual handling techniques, manage work hours and rest periods effectively, and utilize personal protective equipment (PPE).